2014
DOI: 10.1107/s1600577514015203
|View full text |Cite
|
Sign up to set email alerts
|

Lattice design challenges for fourth-generation storage-ring light sources

Abstract: Third-generation low-emittance storage-ring light sources based on double- and triple-bend cells and undulator magnets have been in operation around the world for more than two decades. On the horizon is a new generation based on the multi-bend achromat (MBA) lattice concept promising two to three orders of magnitude higher brightness than is available in today's sources. In this paper, the challenges inherent in designing MBA lattices, as well as potential solutions, are described. Topics covered include latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Low emittance light sources are beginning to produce undulator radiation of interesting spatial distributions [26]. DLSRs are currently proposed with horizontal emittance of order 100 pm rad [38][39][40][41][42][43][44]. Proposed low-emittance light sources and beam lines should be aware of the departure from usual Gaussianapproximated, emittance-dominated photon beams.…”
Section: Discussionmentioning
confidence: 99%
“…Low emittance light sources are beginning to produce undulator radiation of interesting spatial distributions [26]. DLSRs are currently proposed with horizontal emittance of order 100 pm rad [38][39][40][41][42][43][44]. Proposed low-emittance light sources and beam lines should be aware of the departure from usual Gaussianapproximated, emittance-dominated photon beams.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the diffraction-limited storage ring (DLSR) concept has been demonstrated to be feasible for large storage ring like APS, ESRF, and SPring-8 in addition to smaller diameter rings already being built such as MAX-IV in Sweden and SIRIUS in Brazil. 35 From the initial design parameters of the new APS multi-bend achromatic (MBA) ring, 36 the largest time separation will be ∼76 ns which does not significantly impact NRS experiments of isotopes with a few tens of ns half-life like Eu, Sn, and Sm. For the most commonly measured NRS isotope 57 Fe which has 141 ns halflife, this time separation is still good enough for NRIXS experiments which integrate signals from the entire time-collection window.…”
Section: High Pressure Nuclear Resonant Scatteringmentioning
confidence: 99%
“…In order to correct the large natural chromaciticies arising from the strong focusing, sextupoles are usually located in every unit cell. Even so, it was found [12] that the sextupole strengths scale approximately inversely linearly with the natural emittance. Experience [13] indicated that if reducing the natural emittance to a few tens of pm.rad with standard MBAs, unpractically high sextupole gradients or very thick sextupoles (e.g., thicker than quadrupoles) will be needed, leading to an undesirable DLSR design.…”
Section: Introductionmentioning
confidence: 99%